Large Focal Extrapleural Hematoma of Chest Wall: A Case Report - Hohyoung Lee; Sung Ho Han; Min Koo Lee; Oh Sang Kwon; Kyoung Hwan Kim; Jung Suk Kim; Soon-Ho Chon; Sung Ho Shinn (Journal of Trauma and Injury)
Although hemothorax and pneumothorax are common complications seen in rib fractures, focal extrapleural hematoma is quite rare. We report a 63-year-old female patient that developed large focal extrapleural hematoma after falling off a second floor veranda. The patient had sustained 3, 4, 5th costal cartilage rib fractures and a sternum fracture. She had developed suspected empyema with loculations with small amount of hemothorax. She underwent a planned early decortication/adhesiolysis by video assisted thoracoscopic surgery at the 12th post-trauma day due to failed drainage. Unexpectedly, she had no adhesions or any significant retained hematoma mimicking a mass, but was found with the focal extrapleural chest wall hematoma. She was discharged on postoperative 46th day for other reasons and is doing fine today.